HUBUNGAN BAHASA TUBUH GURU DENGAN MOTIVASI BELAJAR BAHASA ARAB SISWA KELAS X - Niswa Ikraama; Maslamah Maslamah (Al-Fakkaar, 2023)
Abstract : This study is a correlational study using quantitative methods aimed at determining the relationship between teacher's body language and motivation to learn Arabic among tenth grade students of Muhammadiyah Al-Kautsar High School Special Program. The independent variable in this study was the teacher's body language, while the dependent variable was the motivation to learn Arabic among tenth grade students of Muhammadiyah Al-Kautsar High School Special Program. The population of this study was all tenth grade students of Muhammadiyah Al-Kautsar High School Special Program, a total of 39 subjects. The samples in this study were tenth grade students of Muhammadiyah Al-Kautsar High School Special Program. The data of this study were collected using a questionnaire (questionnaire) for each variable with a total of 10 points. The results of the analysis of the coefficient of determination show that the teacher's body language influences the students' Arabic learning motivation only 2%, while the remaining 98% is influenced by other factors not investigated in this study. The value of 2% is in a weak range of influence. In addition, the results of calculating the correlation between the teacher's body language and students' motivation to learn Arabic show that the probability is 0.796 > 0.05 (significance level 5%), so Ho is accepted, so it can be concluded that the results of this study show that there is no significant relationship (correlation) between the teacher's body language and students' motivation to learn Arabic among tenth graders at Muhammadiyah Al-Kautsar High School Special Program. Keywords: Body Language and Learning Motivation Abstrak : Penelitian ini merupakan penelitian korelasional dengan menggunakan metode kuantitatif yang bertujuan untuk mencari hubungan antara bahasa tubuh guru dengan motivasi belajar Bahasa Arab Siswa kelas X SMA Muhammadiyah Al-Kautsar Program Khusus Kartasura. Variabel bebas dalam penelitian ini adalah bahasa tubuh guru, sedangkan variabel terikatnya adalah motivasi belajar Bahasa Arab siswa kelas X SMA Muhammadiyah Al-Kautsar Program Khusus Kartasura. Populasi dalam penelitian ini adalah seluruh siswa kelas X SMA Muhammadiyah Al-Kautsar Program Khusus Kartasura yang berjumlah 39 orang. Sedangkan sampel dalam penelitian ini adalah siswa kelas X SMA Muhammadiyah Al-Kautsar Program Khusus Kartasura. Data hasil penelitian ini diperoleh melalui kuesioner (angket) untuk tiap variabelnya dengan jumlah butir item sebanyak 10 nomor. Berdasarkan hasil analisis koefisien determinasi menunjukkan bahwa bahasa tubuh guru mempengaruhi motivasi belajar Bahasa Arab siswa hanya sebesar 2%, dan sisanya 98% dipengaruhi oleh faktor-faktor lain yang tidak diteliti dalam penelitian ini. Nilai 2% tersebut berada dalam tingkatan pengaruh yang lemah. Selanjutnya hasil perhitungan uji hipotesis korelasi bahasa tubuh guru dengan motivasi belajar Bahasa Arab siswa dapat diketahui bahwa probabilitas 0,796 > 0,05 (taraf signifikan 5%), maka Ho diterima sehigga dapat disimpulkan bahwa hasil penelitian ini menunjukkan tidak terdapat hubungan (korelasi) yang signifikan antara bahasa tubuh guru dengan motivasi belajar Bahasa Arab siswa Kelas X SMA Muhammadiyah Al-Kautsar Program Khusus Kartasura Kata Kunci : Bahasa Tubuh dan Motivasi Belajar